Network Interaction of Universities in Higher Education System of Ural Macro-Region - Zborovsky, Garold Efimovich; Ambarova, Polina Anatolyevna (Economy of Regions, 2017)
The subject-matter of the analysis are the characteristics and forms of cooperation between universities of Ural Federal District on the basis of their typology. The purpose of the article is to substantiate the necessity and possibility of network interaction between universities of the macro-region. We prove the importance and potential effectiveness of universities network interaction in the terms of socio-economic uncertainty of the development of Ural Federal District and its higher education. Networking interaction and multilateral cooperation are considered as a new type of inter-universities relations, which can be activated and intensified by strengthening the relations of universities with stakeholders. The authors examine certain concrete forms and formats of network interaction and cooperation between universities and discuss selected cases of new type of relations. In it, they see the real and potential innovation of higher school nonlinear development processes. The statements of the article allow to confirm the hypothesis about the reality of strengthening the network interaction in macro-region. It can transform higher education in the driver of socio-economic development of Ural Federal District; ensure the competitiveness of higher education of the macro-region in the Russian and global educational space; enhance its role in the society; become one of the most significant elements of nonlinear models of higher education development in the country. The authors’ research is based on the interdisciplinary methodology including the potential of theoretical sociology, sociology of higher education, economic sociology, management theory, regional economics. The results of the study can form the basis for the improvement of the Ural Federal District’s educational policy.